Histological changes study of the White rat heart muscle treated with Uranyl acetate - Kawkab S.Najim; Hussain I. Hussain (Tikrit Journal of Pure Science, 2023)
The present investigation aimed to study the histological changes of heart muscle treated with Uranyl acetate for one & two months. The results showed that there was histological changes in the heart muscles , these changes were more sever in animal group treated for two months. Since severe fibrosis was seen with congestion of blood vessel as wear of an increment of fatty degeneration compared with group one which was treated for one month and characterized with the presence of normal not effected region .